Kontribusi Kerjasama Bilateral Indonesia dan Singapura Dalam Sektor Pariwisata Terhadap Perekonomian di Dalam Negeri - Faiq Marsyanda Hibatullah; Kusuma Paksi, Arie (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This research discusses the contributions made between Indonesia and Singapore regarding their cooperation efforts in the tourism sector to the domestic economy. Singapore is a neighbouring country of Indonesia which is one of the largest contributors of tourists in the last 10 years for Indonesia. This is a momentum that is utilised by Indonesia to advance its tourism sector for the domestic economy. The theory used in this research is Interdependence Theory, this theory emphasises that cooperation and mutual benefits can arise from good interdependence. The research method used is qualitative with data collection conducted through internet-based literature studies. This research found that there is a beneficial potential for both countries, especially in the tourism sector given that Indonesia is rich in destinations that are favoured by tourists so as to increase economic figures in the country.